Association between long-term exposure of polystyrene microplastics and exacerbation of seizure symptoms: Evidence from multiple approaches - Ruijin Xie; Xue Xiao; Wenjing Zhao; Yanqi Zhong; Dongqin Wu; Jianrui Dou; Yi Zhao; Yufan Luo; Yingsi Cao; Yuanjin Chang; Wei Xiao; Yuxi Ge; et al. (Ecotoxicology and Environmental Safety, 2025)
Microplastics are tiny plastic particles originating from both commercial product manufacturing and the degradation of larger plastic materials. These particles pose significant risks to environmental and animal health. A growing body of evidence highlights plastic packaging as a major source of microplastic exposure in children, who are particularly vulnerable to these contaminants compared to adults[1]. Despite growing concern, research on the effects of microplastics on human health remains limited, particularly regarding the potential consequences of long-term microplastic exposure. The aim of this study was to investigate the possible association between the neurotoxic effects of prolonged polystyrene microplastic exposure and seizure symptoms, with a special emphasis on the interplay between inflammation and ferroptosis. We hypothesize that long-term ingestion of polystyrene microplastics may disrupt the gut microbiota and induce systemic inflammation, which could subsequently trigger ferroptosis in hippocampal neurons and exacerbate seizure symptoms. Our research contributes significantly to the existing body of knowledge in three key areas. Our investigation makes significant contributions in three key areas: Firstly, by integrating observational pilot cohort studies and interpretable machine learning techniques, we demonstrate that long-term environmental microplastic exposure exposure may affect the independent inflammation-related risk factors of seizures and thereby exacerbate seizure symptoms. Second, through human network toxicology and therapeutic molecular analyses, our results suggest that melatonin may serve as a potential therapeutic intervention, uncovering mechanistic links between inflammation and ferroptosis involved in microplastic-induced seizure exacerbation. Finally, utilizing mice behavioral assays, our results validate how microplastic exposure disrupts iron and lipid metabolism in the brain, triggering neuronal ferroptosis in the hippocampus. Our study not only deepens our understanding of the neurological impacts of microplastic exposure but also identifies viable pathways for therapeutic interventions.